(untitled) (Dhaka University Journal of Biological Sciences, 2014)
A pot experiment was carried out to observe the effect of waste water irrigation on the growth and nutrient status of Kalmi (Ipomoea aquatica) in the nethouse of the Department of Soil, Water and Environment, University of Dhaka. The soil samples were collected from Tejgaon, Rampura, Sitalakhya and from the north?side of Rampura area, the latter is located at a distance from the polluted area and has been used as the control soil. The pots containing the first three soil samples were irrigated with wastewater collected from the adjacent industrial area and control pots were irrigated with tap water. The plants on Tejgaon soil produced the maximum biomass while the plants on Sitalakhya produced the least amount of biomass. The accumulation of toxic metal concentration was found to be the highest in Kalmi grown on Tejgaon followed by Rampura and Sitalakhya. The metal concentration in Kalmi (dry weight basis) ranged between 31 and 408 mg/kg for Zn, 27 to 45 mg/kg for Cu, 0.2 to 5.0 mg/kg for Pb and 0 to 2 mg/kg for Cd, respectively. The concentrations of heavy metals in the Kalmi were higher than the recommended standards in all the treatments except control. DOI: http://dx.doi.org/10.3329/dujbs.v23i1.19820 Dhaka Univ. J. Biol. Sci. 23(1): 1?8, 2014